The relationship between remote diffusion-weighted imaging lesions and the triglyceride-glucose index and clinical outcomes in patients with intracerebral hemorrhage - Lu Wang; Yu Gu; Guoliang Jiang; Chunyan Lei; Potao Zhang; Wen Jiang; Xinglong Yang; Ansong Jin; Qionghua Deng (Frontiers in Neurology)
ObjectiveThis study aimed to observe the relationship between the presence of distal diffusion-weighted imaging (DWI) lesions and triglyceride-glucose (TyG) index and clinical outcome after intracerebral hemorrhage (ICH), and identify the risk factors for DWI lesions in ICH patients.MethodsICH patients at the First Affiliated Hospital of Kunming Medical University were retrospectively collected. Demographic data, laboratory examination, and imaging data of the patients were collected. The patients were divided into two groups based on the presence or absence of distal DWI lesions as determined by magnetic resonance imaging (MRI). Multivariate logistic regression analysis was used to evaluate the risk factors for DWI lesions and clinical outcomes.ResultsAmong 245 ICH patients included in this study, 46 (18.78%) had DWI lesions and 199 (81.22%) did not. We found that the occurrence probability of DWI lesions reached the maximum in the range Q2 of the TyG index. ICH patients with DWI lesions had a similar frequency of death or disability at 90 days compared with patients without DWI lesions. Multivariate logistic regression analysis showed that high fasting glucose (p = 0.039) and hematoma site (p = 0.048) were significant predictors of DWI lesions after ICH. The old age (p < 0.001), higher National Institutes of Health Stroke Scale (NIHSS) score (p < 0.001), and midline shift (p = 0.034) were independent predictors of poor functional outcome at 3 months.ConclusionThere was no definitive correlation between the TyG index and distal DWI lesions in our study. The elevated high fasting glucose levels and hematoma site were significant predictors for DWI lesions after ICH.